Viral Shedding Dynamics in Vaccinated Vs Unvaccinated Populations with New Influenza Variants - Ali, Amna Basharat; Muhammad, Ayra; Abdul Rehman; Shakirullah; Khan, Muhammad Hadi; Mustafa, Khalid (Indus Journal of Bioscience Research, 2025)
Background: Effectiveness of the annual influenza vaccine is mostly quantified by severe disease prevention but its role in influenza shedding dynamics and the period of infectivity, in particular against circulating variants, is a concern of critical importance in understanding the public health. The purpose of the present study was to compare the viral load, shedding period, and the severity of the clinical condition of vaccinated and unvaccinated adults with confirmed influenza infection. Methods: The participants in this observational cohort study (n=72) were evenly divided into two groups based on whether they were vaccinated or not with the influenza virus through laboratory tests (n=36 vaccinated and n=36 unvaccinated). There was close matching of participants in terms of baseline. Nares pharyngeal swabs were taken on a daily basis up to 10 days or until two consecutive negative RT-PCR results were achieved. The results were viral load (Ct values), viral decline rate, total shedding time, culture positive and measures of clinical severity (duration of symptoms and incidence of moderate-severe illness). Results: There was a similarity between groups in terms of baseline characteristics (p > 0.42 all). Viral control was better in the vaccinated group where both the baseline and peak viral load was significantly lower (p=0.002 and p=0.004) and the rate of viral decline was also much faster (2.8 +- 0.6 Ct/day vs 1.9 +- 0.5 Ct/day, p